2020
DOI: 10.1002/dc.24539
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic squamous cell carcinoma transformed from prostatic adenocarcinoma following androgen deprivation therapy: A case report with clinicopathologic and molecular findings

Abstract: Squamous cell carcinoma (SCC) of the prostate is a rare and clinically aggressive entity that may arise de novo or through transformation of prostatic adenocarcinoma, typically following hormonal or radiation therapy. Confirmation of prostatic origin, especially when evaluating a metastatic focus, often requires correlation with clinical and imaging findings, as the morphologic and immunohistochemical features

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…CIC is a transcriptional repressor that constitutively represses certain genes targeted for activation by the EGFR/RAS/MAPK pathway. Lau et al[ 7 ] found a CTNNB1 mutation in their analysis of a transformed SCC. In our own analysis, we found that a RNF43 mutation present in the primary adenocarcinoma was lost in the squamous deposit, but otherwise identical.…”
Section: Discussionmentioning
confidence: 99%
“…CIC is a transcriptional repressor that constitutively represses certain genes targeted for activation by the EGFR/RAS/MAPK pathway. Lau et al[ 7 ] found a CTNNB1 mutation in their analysis of a transformed SCC. In our own analysis, we found that a RNF43 mutation present in the primary adenocarcinoma was lost in the squamous deposit, but otherwise identical.…”
Section: Discussionmentioning
confidence: 99%
“…Our case ts this situation. Recently, Hubert et al [13] detected a TMPRSS2-ERG fusion, among other genetic alterations, by comprehensive genomic pro ling (CGP), supporting a diagnosis of metastatic SCC transformed from prostatic adenocarcinoma following androgen deprivation therapy (ADT).…”
Section: Discussionmentioning
confidence: 99%
“…This analysis encompasses the examination of tissue architecture, cellular morphology, stromal-epithelial interactions, and the presence of any atypical features. Recent advancements in histopathological techniques, including immunohistochemistry and molecular pathology, have further refined our understanding of prostatic diseases [3].…”
Section: Introductionmentioning
confidence: 99%